Compression of illumination-adjustable images - Wong, Tien-Tsin; Leung, Chi-Sing (IEEE transactions on circuits and systems for video technology, 2003)
The image-based modeling and rendering (IBMR) approaches allow the time complexity of synthesizing novel images to be independent of scene complexity. Unfortunately, illumination control (relighting) is no longer trivial under the image-based framework. To relight the image-based scenery, the scene must be captured under various illumination conditions. This drastically increases the data volume. Hence, data compression is a must. In this paper, we describe a compression algorithm for an illumination-adjustable image representation. We focus on compressing constant-viewpoint images. A divide-and-conquer approach is proposed. The compression algorithm consists of three parts which exploit the intrapixel, interpixel, and interchannel data correlations. Experimental result shows that the proposed method not just effectively compresses the data but also outperforms standard image and video coding methods.